2005
DOI: 10.1089/aid.2005.21.907
|View full text |Cite
|
Sign up to set email alerts
|

Sampling Designs for HIV Molecular Epidemiology with Application to Honduras

Abstract: Proper sampling is essential to characterize the molecular epidemiology of human immunodeficiency virus (HIV). HIV sampling frames are difficult to identify, so most studies use convenience samples. We discuss statistically valid and feasible sampling techniques that overcome some of the potential for bias due to convenience sampling and ensure better representation of the study population. We employ a sampling design called stratified cluster sampling. This first divides the population into geographical and/o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…This is reflected in the diverse study population composition based on self-reported sexual identity (table 1). To ensure better representation of this MSM study population, future sampling should consider the implementation of stratified cluster sampling techniques, as described elsewhere [35]. Second, given that 12 different clinic sites and hundreds of field personnel participated in the surveys in all 6 cities, it is possible that differences in volunteer recruitment and study interview administration may have existed.…”
Section: Discussionmentioning
confidence: 99%
“…This is reflected in the diverse study population composition based on self-reported sexual identity (table 1). To ensure better representation of this MSM study population, future sampling should consider the implementation of stratified cluster sampling techniques, as described elsewhere [35]. Second, given that 12 different clinic sites and hundreds of field personnel participated in the surveys in all 6 cities, it is possible that differences in volunteer recruitment and study interview administration may have existed.…”
Section: Discussionmentioning
confidence: 99%
“…The demographics of the study population closely matched that of the published sampling design. 29 The median age of the study population was 31 years (range 15-64 years); 53% were male and 47% were female. The predominant route of HIV transmission was heterosexual (86%), 132 samples were from the general population, 11 samples from FSW and 29 samples from Garifunas; and the remaining 28 samples were collected from MSM.…”
Section: Characteristics Of the Study Populationmentioning
confidence: 98%
“…To ensure a good representation of the population with HIV-infected persons in Honduras, we followed a published sampling strategy for representative HIV genotyping studies in Honduras. 29 The study included samples from general population, Garifunas (an ethnic group of African descent that migrated from Caribbean islands to the northern coast of Honduras), men who have sex with men (MSM) and female sex workers (FSW). Samples from the general population were collected using a convenience sampling strategy in the three major clinical centers of the country, Centro de Salud Miguel Paz Barahona in San Pedro Sula, Hospital Escuela and Instituto Nacional del Tórax in Tegucigalpa.…”
Section: Study Populationmentioning
confidence: 99%
“…Statistical methods to be developed for CCASAnet include sensitivity analysis approaches for causal inference, 17 techniques for adjusting lab variables to enable fairer cross-site comparison, 18 and unbiased and efficient sampling methods for studying the molecular epidemiology of HIV. 19 What is the attrition rate likely to be?…”
Section: What Does It Cover and Who Is In The Sample?mentioning
confidence: 99%